The Effect of Using Task Based Learning Method on Student’s Achievement in Reading Comprehension of Descriptive Text. - Muhamad Ihsan Deliansyah Yuliawati (Universitas Sulawesi Barat, 2021)
Descriptive Text is a kind of text with a purpose to give information. The context of this kind of text is the description of a particular thing, animal, person, or others, for instance: our pets or a person we know well. Unfortunately, the students feel hard to find out because no strategy or method to read descriptive text so makes the students boring. The objective of this research is to find out whether task-based learning teaching students’ reading comprehension of descriptive text to XI grade students of MA Darul Ihsan Cibungbulang Bogor. The research used a quantitative method with a quasi-experimental design by applying pre-test and post-test design. In this research, the writer only uses one class as the sample by using the purposive sampling technique. In collecting the data, the writer use tests as an instrument. The data was analyzed by using a t-test. The result of this research showed that using task-based learning method effective in teaching reading comprehension of descriptive text. It can be seen from the significance t-test from students’ pre-test and post-test scores that is 2.450>2.056. Based on the statistical calculation, using task-based learning method reached t calculation of 2.450 which was higher than t table of 2.056 at a significance level of 5%. It also stated a significant increase in mean score between students’ pre-test score (51.8) and post-test score (80). The statistical hypothesis revealed that there were differences between both tests. Therefore, using the task-based learning method can be effective for students’ reading comprehension of descriptive text.